Analysis of Significant Wave Heights Based on Seasons in the Seram Sea - Yulian Yudha Dwi Pamungkas; Delly Dominggas Paulina Matruty; Simon Ubalawony (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to observe the seasonal variation of wave height in the waters of Seram Island. The software used in this research are Arcgis and SeaDAS. Numerical and spatial processing tools used in this study using SeaDAS software. The monthly average is then taken using GIS software as a geographic information system processing that will offer an overview of the state of the study area, present research results, and interpolate between parameters.